DESIGN OF TIRE PRESSURE MONITORING SYSTEM USING A PRESSURE SENSOR BASE - Lukman Medriavin Silalahi; Mudrik Alaydrus; Agus Dendi Rochendi; Muhtar Muhtar (SINERGI, 2019)
Currently, the Tire Pressure Monitoring System (TPMS) only monitors the condition of a tire pressure. However, there are no particular reactions taking place after the value of its tire pressure is discovered. In fact, the value of a tire pressure determines driving comfort and safety Therefore, this research proposed a method to integrate a TPMS and a Pressure Sensor Base (PSB) with a particular reaction required to fulfill tires automatically. The proposed TPMS has an electronic device unit directly attached to a tire’s valve. This unit includes pressure sensors, microcontrollers, Bluetooth transmitters and batteries. An alert system is generated whenever tire pressure exceeds the maximum or minimum safe pressure level. Moreover, if the pressure measured is below the lowest level of the desired pressure, it will automatically activate the compressor. Several experiments have been carried out to analyze the proposed system. The integrated TPMS has proven to be able to be an alternative tool for the automotive sector to keep maintaining the tires and to improve a driving comfort and safety.